EFFECT OF OSMOTIC PRESSURE AND pH ON THE SHORT-TERM STORAGE AND FERTILITY OF BROILER BREEDER SPERM - A. Latif, A. Ijaz, M. Aleem and A. Mahmud1 (Pakistan Veterinary Journal, 2005)
Effect of osmotic pressure and pH on the short-term storage of cockerel semen using modified Van Wambeke milk based extender ‘Experimental Extender’ was studied. Six broiler breeder cockerels were used and 7 ejaculates were collected from each cockerel every second day. In experiment 1, semen was diluted in the Experimental Extender with osmotic pressures 350, 375 or 400 mOsm and pH 7.0 and stored at 5ºC. In experiment 2, semen was diluted in the Experimental Extender with osmotic pressure 375 mOsm and pH 6.4, 7.0 or 7.4 and stored at 5ºC. The effect of osmotic pressure and pH on percentage motility, sperm speed and clumping was evaluated at 4, 24 and 48 hr. There was a significant difference (P<0.05) among the osmotic pressures evaluated in terms of percentage motility, speed of sperm cells and extent of clumping during 48 hr of semen storage. The 375 mOsm osmotic pressure was found to be best (P<0.05) for the short-term storage of cockerel semen. There was a significant difference (P<0.05) among different pH values evaluated in terms of percentage motility after 24 and 48 hr of semen storage. pH 7.0 and/or 7.4 were found to be optimum (P<0.05) for the short-term storage of cockerel semen. Fertility/hatchability was higher (88%, P<0.05) when sperm were stored in the Experimental Extender with osmotic pressure 375mOsm and pH 7.0, and in Fecondil (86%) as compared to normal saline (79%). In conclusion, the Experimental Extender with 375 mOsm osmotic pressure and pH 7.0 is suitable for the short-term storage of poultry semen and it improves fertility of the spermatozoa as well.